Credit Risk in the Euro Area Compared to Other European Union Countries - Radosław Pastusiak; Magdalena Jasiniak; Anna Pluskota (Annales Universitatis Mariae Curie-Skłodowska Sectio H, Oeconomia, 2022)
Theoretical background: The article examines the microeconomic and macroeconomic determinants of credit risk in the European Union countries divided into two groups: countries that own the euro and countries outside the euro area.